Magyarországi középvárosok imázs vizsgálata - Győrfi, Katalin; Szabó-Hevér, Judit; Király, Zsolt; Tamus, Antalné (Acta Carolus Robertus, 2011)
In our days a settlement may become successful and may take a step on the road of the development if it can take advantage of its available resources maximally, that is it puts up a good show. The economic and social interpretation of regional – in a present case urban – performance is equally legitimate, in this manner under its factors not only the incomes, the infrastructural provision, other economic and social statistical indicators are to be understood, but the single functions, services, conditions, part and gap markets of settlements (cities) too. In the life of the settlements it’s important to provide services on high level, the public safety, the natural environment and the local residents’ hospitality be suitable and the inclination of undertaking and the settlement image evolved by the potential exterior investors play an important in the development. We analyse these contexts in our paper with the help of secondary examination and a primer research (questionnaire image examination) focused on three cities: Gyöngyös, Kazincbarcika and Kiskunfélegyháza. Our aim is to reveal the differences between the performances of cities and their reasons, and to shed light on it, that singly the observance of statistical index-numbers are short and the image of the settlement and the elements influencing it are important too.